IS DANIEL A MONSTER? REFLECTIONS ON DANIEL A. BELL AND WANG PEI’S “SUBORDINATION WITHOUT CRUELTY” THESIS - Ebert, Rainer; Giroux, Valéry; Pepper, Angie; Voigt, Kristin (Les ateliers de l'éthique / The Ethics Forum, 2022)
Daniel Bell and Wang Pei’s recent monograph, Just Hierarchy, seeks to defend hierarchical relationships against more egalitarian alternatives. This paper addresses their argument, offered in one chapter of the book, in favour of a hierarchical relationship between human and nonhuman animals. This relationship, Bell and Pei argue, should conform to what they call “subordination without cruelty:” it is permissible to subordinate and exploit animals for human ends, provided that we do not treat them cruelly. We focus on three aspects of their view: their argument for a hierarchical view; their understanding of cruelty; and their account of the heightened duties they claim we owe to nonhuman animals who are intelligent, domesticated, and/or “cute.” We argue that the reasons that Bell and Pei offer fail to support their conclusions, and that, even if one accepts a hierarchical view, the conclusions that Bell and Pei draw about the permissibility of practices such as killing animals for food do not follow. We conclude by emphasizing philosophers’ responsibility to thoroughly test their arguments and to engage with existing debates, especially when the practices they seek to justify involve harms of great magnitude.